Inhibition of minority transport for elevating the thermoelectric figure of merit of CuO/BiSbTe nanocomposites at high temperatures. Issue 113 (25th November 2016) - Li, Yuanyue; Liu, Guoxia; Qin, Xiaoying; Shan, Fukai
Abstract : In BiSbTe based composite with 0.2 vol% of CuO nanoinclusions, thermoelectric figure of merit increases monotonically and largest ZT = 1.37 was obtained at 496 K by inhibiting the transport of minorities at introduced asymmetric interface potentials. Abstract : Achieving a large thermoelectric figure of merit ( ZT ) value at elevated temperatures for Bi2 Te3 -based materials is significant for low-grade waste-heat (∼400–500 K) recovery applications. Here, we show that in Bi0.4 Sb1.6 Te3 based composites incorporated with 0.2 vol% CuO nanoinclusions, the introduced asymmetric interface potentials can effectively inhibit the transport of minorities through stronger scattering than majorities, as well as the energy filtering effect, thus resulting in an obvious increase (∼8% rise) of power factor at high temperatures. In addition to enhanced phonon scattering at interfaces and nanoinclusions, the reduced thermal conductivity (∼65% decline) at elevated temperatures can be attributed to inhibition of bipolar contributions through strong scattering of minorities at the interface potentials. Consequently, in BiSbTe-based thermoelectric systems with 0.2 vol% CuO, a largest ZT = 1.37 is achieved at 496 K, which is ∼40% larger than that of the BiSbTe matrix at the same temperature.